The Integration of Alternative Dispute Resolutions Institutions in the Financial Services Sector with POJK No. 61/POJK.07/2020 - Muhammad Fikri Aufa; Fadia Fitriyanti (Veteran Law Review, 2022)
Financial institutions and consumers/customers have more than a contractual relationship. Financial institutions and consumers build trusting relationships. These 2 financial services businesses are used for financial services dispute resolution. The settlement includes Banking, Insurance, Capital Market, Guarantee, Pension Fund, and Financing and Pawnshops. In 2020, OJK issued POJK No. 61/POJK.07/2020 on Alternative Institutions for Financial Services Sector Disputes. The newest Financial Services Authority Regulation divides dispute resolution into 6 financial services sectors. This time, it's 1 alternative dispute resolution institution for financial services. This study examines the unification principle's applicability. Integration of conflict resolution organizations, authorities, and methods in the financial services industry. Legal normative research is used. This study uses primary and secondary legal sources from laws and books/journals. This study shows that alternative dispute resolution entities in the financial services sector have implemented unification and integration to conflict resolution.